(untitled) (Integral Research, 2024)
Kiran Nagarkar (1942-2019) was born in Bombay in 1942. He was a celebrated Marathi and English novelist, post independent writer, Journalist, copywriter, screenwriter and playwright. He was identified as a multiethnic, investigational, multifaceted genius, impudent and unrealizable writer. In Indian English literature, he has carved his name to a greater extent as a remarkable contemporary writer. He completed his graduation from Pune University in 1964 and post-graduation from Bombay University in 1967 in English literature. He was the outstanding representative of contemporary Indian literature. His works are a target of philosophical appraisal due to the mixture of his variety of post colonialism. His writing is concentrated and thought aggravating. His literary career illumines through his philological selections and dogmatic dissertation. Bedtime Story is a play based on an epic Mahabharata written by eminent contemporary writer Kiran Nagarkar. He can challenge the established norms and to re-write the ancient narratives with fresh perspective. He delineates the real social conditions, ancient cultures and valuable ethics of traditional Indian society. Nagarkar restored the past through his technique of retelling Indian myths of epic Mahabharata. Bedtime Story reveals modern approach to his works and attempts to offer new insight. The main attempt of the researcher is to explore the indications of contemporary Indian history, legends and politics through the Hindu epic the Mahabharata considering Kiran Nagarkar’s well reputed play Bedtime Story.